Processable Thiophene‐Based Polymers with Tailored Electronic Properties and their Application in Solid‐State Electrochromic Devices Using Nanoparticle Films. (13th May 2021) - Moreira, Tiago; Maria, Francesca Di; Zangoli, Mattia; Fabiano, Eduardo; Manet, Ilse; Mazzaro, Raffaello; Morandi, Vittorio; Marinelli, Martina; Gigli, Giuseppe; Parola, António Jorge; Laia, César A. T.; Barbarella, Giovanna
Abstract: The development of semiconductor polymers for electronic applications requires tailored synthetic strategies to obtain materials with tunable electronic properties and morphology to enhance their properties. Towards this goal, here is reported the expedient synthesis of a novel class of thiophene‐based electrochromic polymers, processable in organic solvents and as nanoparticles (NPs) in water. Their characterization and application in flexible solid‐state electrochromic devices (ECDs) are described. All polymers have a repeat unit made of the same linear thienyl–phenyl–thienyl–thienyl fragment. The tuning of the electro‐optical properties is achieved by introducing alkyl or alkoxy substituents in thiophene and/or by the presence of either CHCH or CH2 CH2  linkers connecting the repeat units and acting as conjugation modulators. The ECDs display a bright yellow or red/magenta color in the neutral state and dark blue in the oxidized state. Redox potentials, color contrast, switching time, and stability of the devices are reported, and it is demonstrated that the use of NPs films spray‐coated from water instead of cast films from chloroform significantly improves their performance. Density functional theory calculations allow to elucidate the relationship between polymer structure and electrochromic properties and shed light on electronic structure changes upon oxidation, in agreement with spectroelectrochemistry. Abstract : A new class of polymers combining a simple structure, facile synthesis, tunable electrochromic properties, and nanostructuration ability is reported. It is demonstrated that the use of nanoparticle films spray‐coated from water dispersions instead of cast films from chloroform solutions leads to enhancement of the final electrochromic device (ECD) performance in terms of switching time, charge consumption, optical contrast, and durability.